The epidemiology and associated factors of non-exclusive breastfeeding: a comparative cross-sectional study of livelihood-secure and insecure areas - Negesse, Ayenew; Girma, Tsinuel; Desalegn, Beruk Berhanu; Kerac, Marko; Berhane, Melkamu (Frontiers in Nutrition, 2024)
Introduction: Regardless of national commitment, non-exclusive breastfeeding (NEBF) is a public health problem which is worsening over time. It can be associated with socio-demographic, economic and environmental factors, and may vary depending on livelihood security. Hence, this study aimed to determine the magnitude of NEBF and identify its associated factors by considering two areas with varied degrees of livelihood security.Method: This study represented a comparative cross-sectional survey of 1060 under-six-month (u6m) infant-mother pairs. Both descriptive and analytic statistics were done using STATA version 17 packages. A binary logistic regression was used to identify associated factors of NEBF. The odds ratio (OR) with a 95% confidence interval (CI) was used to measure the significance of the association at pvalue <0.05.The pooled magnitude of NEBF was 51% (95% CI: 48.0, 54.0) being 53.1% (95% CI: 49.2, 57.0), and 48.1% (95% CI: 43.4, 52.8) in livelihood-secure and livelihood-insecure areas, respectively.Maternal lack of remembering infant's birth date (AOR=2.4; 95% CI=1.15-4.40) had highest odds of NEBF while household heads with tertiary education (AOR=0.14; 95% CI=0.01-0.54) and poorest households (AOR=0.43; 95%CI=0.20-0.82) had low odds of NEBF in livelihood-secure areas, but not in livelihood-insecure areas. Moreover, mothers with male infants (AOR=1.9; 95% CI=1.18-2.92) had high odds of NEBF in livelihood-insecure areas, but not in livelihood-secure areas. Infants 2 to < 4-month-old (AOR=8.5; 95% CI=3.47-18.63) and 4 to <6-month (AOR=22.2; 95% CI=8.02-51.97) in livelihood-secure areas as well as infants 2 to < 4-month-old (AOR=4.3; 95% CI=1.29-11.67) and 4 to <6-month (AOR=8.3; 95% CI=2.44-22.39) in livelihood-insecure areas had high odds of NEBF.Over half of mothers were practicing NEBF, which represents a failure to meet national and international targets. Area vulnerability to livelihood-security modifies factors of NEBF. Male infants in insecure areas, infants of unknown age in secure areas, and infants aged 2 months or older, regardless of setting, were more vulnerable to NEBF. However, households with the lowest wealth and higher household head educational status in livelihood-secure areas less vulnerable to NEBF. Hence, livelihood-based interventions targeting mothers of 2 to <6-month infants, with emphasis on these factors, may help address and reduce NEBF.